FRI0123 SAFETY PROFILE OF BARICITINIB FOR THE TREATMENT OF RHEUMATOID ARTHRITIS UP TO 8.4 YEARS: AN UPDATED INTEGRATED SAFETY ANALYSIS. (2nd June 2020) - Genovese, M. C.; Smolen, J. S.; Takeuchi, T.; Burmester, G. R.; Deberdt, W.; Schlichting, D.; Song, H.; Mo, D.; Walls, C.; Winthrop, K.
Abstract : Background: Baricitinib (bari) is an oral selective inhibitor of Janus kinase (JAK) 1 and 2, approved for the treatment of moderately to severely active rheumatoid arthritis (RA) in adults. Objectives: Here we update the drug's safety profile with data up to 8.4 years of treatment. Methods: Long-term safety of bari was assessed from 9 completed randomized trials (5 Ph3, 3 Ph2, 1 Ph 1b) and 1 ongoing long-term extension (LTE) study. Incidence rates (IR) per 100 patient-years (PY) were calculated for all patients with RA treated with ≥1 dose of bari through 1-Sep-2019 (All-Bari-RA analysis set). IRs for deep vein thrombosis (DVT), pulmonary embolism (PE), and DVT and/or PE (DVT/PE) were also calculated for groups of patients while receiving bari 2mg or bari 4mg within All-Bari-RA. Major adverse cardiovascular events (MACE) were adjudicated in 5 phase 3 studies and the LTE. Results: 3770 pts received bari for 13, 148 PY, with a median and maximum exposure of 4.2 and 8.4 years, respectively. Overall IRs per 100 PY were: for any treatment-emergent adverse event (AE)(25.8); serious AE (including death)(7.2); temporary interruption due to AE (9.5); permanent discontinuation due to AE (4.8); death (0.52); serious infection (2.7); opportunistic infection (0.44) (excluding tuberculosis [TB], including multidermatomal herpes zoster [HZ]); TB (0.15); HZ (3.0); MACE (0.50); DVT (0.31); PE (0.24); DVT/PE (0.45); malignancies excluding non-melanoma skin cancer (NMSC) (0.90); NMSC (0.33); lymphoma (0.06); and gastrointestinal perforation (0.04). Incidence rates (IR)[95% confidence intervals] for patients while receiving bari 2mg (N=1077) and bari 4mg (N=3400) were DVT 2mg (0.38) [0.18, 0.73] and 4mg (0.30) [0.21, 0.43]; PE 2mg (0.26) [0.09, 0.56] and 4mg (0.25) [0.16, 0.36]; and DVT/PE 2mg (0.47) [0.23, 0.84] and 4mg (0.46) [0.34, 0.61]. IRs for death tended to increase in later time intervals (beyond 192 weeks). No particular cause of death contributed to this increase. For all other safety topics of interest, across 48-week treatment intervals, IRs remained stable over time. Across safety topics, IRs were consistent with previous analyses 1, 2 . Conclusion: In this update with 3, 021 additional PY of exposure, bari maintained a safety profile similar to that previously reported, 1, 2 with no increase of IRs across safety topics through exposures up to 8.4 years. References: [1]Smolen JS et al. J Rheumatol. 2019 Jan;46(1):7-18 [2]Genovese MC et al. Ann Rheum Dis. 2019 78(supp. 2):A308 Disclosure of Interests: Mark C. Genovese Grant/research support from: Abbvie, Eli Lilly and Company, EMD Merck Serono, Galapagos, Genentech/Roche, Gilead Sciences, Inc., GSK, Novartis, Pfizer Inc., RPharm, Sanofi Genzyme, Consultant of: Abbvie, Eli Lilly and Company, EMD Merck Serono, Genentech/Roche, Gilead Sciences, Inc., GSK, Novartis, RPharm, Sanofi Genzyme, Josef S. Smolen Grant/research support from: AbbVie, AstraZeneca, Celgene, Celltrion, Chugai, Eli Lilly, Gilead, ILTOO, Janssen, Novartis-Sandoz, Pfizer Inc, Samsung, Sanofi, Consultant of: AbbVie, AstraZeneca, Celgene, Celltrion, Chugai, Eli Lilly, Gilead, ILTOO, Janssen, Novartis-Sandoz, Pfizer Inc, Samsung, Sanofi, Tsutomu Takeuchi Grant/research support from: Eisai Co., Ltd, Astellas Pharma Inc., AbbVie GK, Asahi Kasei Pharma Corporation, Nippon Kayaku Co., Ltd, Takeda Pharmaceutical Company Ltd, UCB Pharma, Shionogi & Co., Ltd., Mitsubishi-Tanabe Pharma Corp., Daiichi Sankyo Co., Ltd., Chugai Pharmaceutical Co. Ltd., Consultant of: Chugai Pharmaceutical Co Ltd, Astellas Pharma Inc., Eli Lilly Japan KK, Speakers bureau: AbbVie GK, Eisai Co., Ltd, Mitsubishi-Tanabe Pharma Corporation, Chugai Pharmaceutical Co Ltd, Bristol-Myers Squibb Company, AYUMI Pharmaceutical Corp., Eisai Co., Ltd, Daiichi Sankyo Co., Ltd., Gilead Sciences, Inc., Novartis Pharma K.K., Pfizer Japan Inc., Sanofi K.K., Dainippon Sumitomo Co., Ltd., Gerd Rüdiger Burmester Consultant of: AbbVie Inc, Eli Lilly, Gilead, Janssen, Merck, Roche, Pfizer, and UCB Pharma, Speakers bureau: AbbVie Inc, Eli Lilly, Gilead, Janssen, Merck, Roche, Pfizer, and UCB Pharma, Walter Deberdt Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Douglas Schlichting Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Hongsuk Song Employee of: Syneos Health under contract to Eli Lilly and Company, Daojun Mo Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Chad Walls Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Kevin Winthrop Grant/research support from: Bristol-Myers Squibb, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, Galapagos, Gilead, GSK, Pfizer Inc, Roche, UCB